= 9n + 63
generate the first few terms using the recursive equation
f(1) = 72
f(2) = 72 + 9 = 81
f(3) = 81 + 9 = 90
f(4) = 90 + 9 = 99
the sequence is 72, 81, 90, 99, .....
This is an arithmetic sequence whose n th term formula is
=
+ (n - 1 )d
where
is the first term and d the common difference
d = 99 - 90 = 90 - 81 = 81 - 72 = 9 and
= 72
= 72 + 9(n - 1) = 72 + 9n - 9 = 9n + 63 ← explicit formula
Answer: I am pretty sure the answer is
g(x) = (x+3)^2 +9
Consider brainleist?
Hope this helped
:D
Answer:
-43
Step-by-step explanation:
-35 + 7 + (-15)
-35 + 7 - 15
-50 + 7
<u>= -43</u>
-20/48 x 6 =
![\frac{-20}{48}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-20%7D%7B48%7D%20)
x
![\frac{6}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B1%7D%20)
I would cancel out the 6 in the numerator and the 48 in the denominator
Now I have <u />
![\frac{-20}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-20%7D%7B8%7D%20)
or <u />
![\frac{-5}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%7D%7B2%7D%20)
reduced.
-5 ÷ 2 = -2 1/2 and that is the answer in simplest form
Answer:
(-7.5, 0) x intercept
(0, 5.5) y intercept
Step-by-step explanation:
The x intercept is where it crosses the x axis
It crosses at (-7.5, 0)
The y intercept is where it crosses the y axis
It crosses at (0, 5.5)